Treatment of Pregnant Women With Fear of Childbirth Using EMDR Therapy: Results of a Multi-Center Randomized Controlled Trial - Baas, M. A. M.; van Pampus, M. G.; Stramrood, C. A. I.; Dijksman, L. M.; Vanhommerig, J. W.; de Jongh, A. (Frontiers in Psychiatry, 2022)
Fear of Childbirth (FoC) occurs in 7.5% of pregnant women and has been associated with adverse foeto-maternal outcomes. Eye Movement Desensitization and Reprocessing (EMDR) therapy has proven to be effective in the treatment of posttraumatic stress disorder (PTSD) and anxiety, however, its effectiveness regarding FoC has not yet been established. The aim was to determine the safety and effectiveness of EMDR therapy for pregnant women with FoC. This single-blind RCT (the OptiMUM-study, www.trialregister.nl, NTR5122) was conducted in the Netherlands. Fear of Childbirth was defined as a score ≥85 on the Wijma Delivery Expectations Questionnaire (WDEQ-A). Pregnant women with FoC and a gestational age between 8 and 20 weeks were randomly assigned to EMDR therapy or care-as-usual (CAU). The severity of FoC was assessed using the WDEQ-A. Safety was indexed as worsening of FoC symptoms, drop-out, serious adverse events or increased suicide risk. We used Linear Mixed Model analyses to compare groups. 141 women were randomized (EMDR n=70; CAU n=71). No differences between groups were found regarding safety. Both groups showed a very large (EMDR d=1.36) or large (CAU d=.89) reduction of FoC symptoms with a mean decrease of 25.6 (EMDR) and 17.4 (CAU) points in WDEQ-A sum score. No significant difference between both groups was found (p=0.83). At posttreatment 72.4% (EMDR) versus 59.6% (CAU) no longer met the criteria for FoC. In conclusion, the results are supportive of EMDR therapy as a safe and effective treatment of FoC during pregnancy, albeit without significant beneficial effects of EMDR therapy over and above those of CAU. Therefore, the current study results do not justify implementation of EMDR therapy as an additional treatment in this particular setting.